2003
DOI: 10.1021/jp036416r
|View full text |Cite
|
Sign up to set email alerts
|

Condensation of Frontier Molecular Orbital Fukui Functions

Abstract: A comparison of the regional Fukui index evaluation within the frontier molecular orbital (FMO) Fukui functions is presented. The atoms-in-molecules (AIM) real space-based condensation scheme is compared against a basis set-based condensation scheme and the reliability of the produced reactivity trends is compared. The AIM condensation scheme turns out to give the best results. Furthermore, the AIM atom condensed Fukui indexes can be formally proven to be nonnegative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(92 citation statements)
references
References 21 publications
0
92
0
Order By: Relevance
“…Naturally, it remains possible to use the weight functions based on the entire density. Condensed FMO Fukui functions using the FMO density and the QCT weight functions derived from the total density have been studied in detail by Bulat et al 77 As explicitly indicated, w A QCT ͑r , N͒ depends on the number of electrons in the molecule. The atomic basins are well known to change upon changing the number of electrons in the molecule.…”
Section: Frontier Molecular Orbital Approachmentioning
confidence: 99%
“…Naturally, it remains possible to use the weight functions based on the entire density. Condensed FMO Fukui functions using the FMO density and the QCT weight functions derived from the total density have been studied in detail by Bulat et al 77 As explicitly indicated, w A QCT ͑r , N͒ depends on the number of electrons in the molecule. The atomic basins are well known to change upon changing the number of electrons in the molecule.…”
Section: Frontier Molecular Orbital Approachmentioning
confidence: 99%
“…In fact, Roy et al [34][35][36][37][38] have shown that the latter is more reliable than MPA for calculating local reactivity descriptors and also produces nonnegative condensed Fukui function values. A lot of other work on nonnegative Fukui functions has been reported, [39][40][41] and it can be concluded that the Fukui function itself can be negative, although condensed Fukui functions cannot be negative, except in certain cases.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The second one, f−(r), has been associated to reactivity for an electrophilic attack so that this function measures the intramolecular reactivity at the site r toward an electrophilic reagent [24]. Condensation to atoms is achieved through integration within the kth-atomic domain Ωk [30,31]:…”
Section: Theoretical Backgroundmentioning
confidence: 99%